Efeito neuroprotetor e anti-inflamatório do nitrosilo complexo de rutênio em ratos Wistar submetidos à isquemia/reperfusão cerebral global incompleta - Justi, Fátima Virgínia Gama (2022)
Cerebrovascular accident (CVA), also known as stroke, is the disease with the second highest mortality rate in Brazil and in the world, and the ischemic type (stroke) is the most common among the cases. The ischemia/reperfusion (I/R) process is the main factor for tissue damage from stroke. The ruthenium complex nitrosyl (Rut-bpy) is a nitric oxide (NO) donor metallopharmaceutical, which has a relaxing action on vascular smooth muscle. In this study, we evaluated whether the treatment with Rut-bpy has a neuroprotective effect after 7 days of the incomplete global I/R process in adult rats, induced by bilateral occlusion of the common carotids (ischemia) for 20 minutes, followed by reperfusion. Male Wistar rats, with an average weight of 250-300g, were divided into 3 groups: Sham + Saline (S+S); I/R + Saline (I/R+S); I/R + Rut-bpy (I/R+R), with administration of a single dose of Rut-bpy (100 mg/kg) diluted in saline with intraperitoneal administration after of the onset of ischemia. All protocols were approved by the CEUA-UFC, with protocol No. 3574290120. For the induction of I/R, the bilateral common carotid arteries were occluded by compression. On the seventh postoperative day, the animals were euthanized with collection of brain tissue for evaluation of the infarction area by the TTC method, obtaining the hippocampus for the analysis of BDNF, TNF-α and IL-1β, from blood, for plasma evaluation of TNF-α, IL-1β, IL-6, and MPO in addition to serum for MDA analysis. The single analysis of variance test (ANOVA) and then Tukey's test of multiple comparisons were used to confirm statistically significant data (P < 0.05). In the TTC assay, the total unstained area was significantly (P < 0.05) smaller in the I/R+R group when compared to the I/R+S group. Higher concentrations of BDNF were observed in the I/R+S group animals (P < 0.05), in relation to the I/R+R and S+S groups. TNF-α and IL-1β levels in the hippocampus were significantly lower in the I/R+R group when compared to the I/R+S group (P = 0.01; P = 0.0004, respectively). Regarding plasma levels of pro-inflammatory cytokines, a reduction in the levels of TNF-α, IL-1β, IL-6, and MPO was observed in the I/R+R group compared to the I/R+S group (P = 0.01; 0.0001; 0.0007; 0.004, respectively). Serum levels of MDA did not show significant differences between groups. We conclude that treatment with Rut-byp demonstrated an anti-inflammatory and neuroprotective effect in the model of incomplete global brain I/R in Wistar rats.